FAKTOR-FAKTOR YANG BERHUBUNGAN TINDAKAN AWAL PADA PENDERITA INFEKSI DENGUE DI KELURAHAN SENDANGMULYO - Fitri Nengsih Chaniago; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2018)
The case of dengue infectious in Semarang increased since 2015-2016. Tembalang was first ranked based on IR (216,45) and CFR (1,54). While IR of Sendangmulyo 210,42 and CFR of Sendangmulyo 1,23. The condition of a person suffering from dengue virus is relatively same as the usual fever condition, so that required laboratory test for follow-up.This study aims to analyze factors associated with initial actions of dengue infectious patients at Sendangmulyo.This research is quantitative approach with survey analytic method and cross sectional study design. The sample was taken by purposive sampling method as much as 68 people. Data were collected by interview method using questionnaire, while the research result use univariat and bivariate analysis.Respondents were young adults and middle adulthood balanced, male repsonden (69,1%). Patients with dengue infection (DHF) 80,9%. Respondents have married status 98.5%. Level of education is at senior high school (35,3%), most of work is entrepreneurship (32,4%). Small family members is 75,0%. Family income above UMR is 85,3%. Bivariateanalysis showed that family support variables (p=0,018) were associated with initial action in dengue infectious patients, age (p=1,000), sex (p=1,000), type of dengue infection (p=1,000) marriage (p=1,000), education (p=1,000), occupation (p=1,000), family member (p=1,000), income (p=1,000), knowledge (p=1,000), access availability (p=1,000), and perception (p=0,674) were not associated with initial action in dengue infectious patients.